Effect of grass-legume silage on production and milk composition of Friesian cross cows in Imbo region of Burundi (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study determined the effects of feeding Cenchrus purpureus- Velvet bean, or Maize stalk- Velvet bean silage on milk production and quality. The one-way analysis of variance (ANOVA) in R4.4.1 software was used for data analysis. Results from the study showed that there was a significant difference (P